Strategic and management plans for an agricultural water supply system in Southern Italy - Coppa A.; Cervarolo G.; Mendicino G.; Senatore A.; Versace P. (Drought management: scientific and technological innovations, 2008)
According to European policy on drought and water scarcity a proactive approach is proposed to cope with drought phenomena in one of the most important agricultural areas in southern Italy. First, a strategic plan is developed in order to reduce the vulnerability of the irrigated area by means of long-term measures. Then, according to the implemented strategic plan, a management plan and a contingency plan are developed to schedule short-term measures to be adopted in case of water scarcity. Through appropriate early warning indicators different conditions were defined (Normal, Pre-Alert, Alert and Alarm) with the aim of determining the best mix of measures to be chosen.
1. International Conference Drought Management: Scientific and Technological Innovations, 2008/06/12-14, Zaragoza (Spain)